Evaluasi Efektivitas Daun Bayam Merah (Amaranthus tricolor L.) Berdasarkan Waktu Perendaman sebagai Pewarna Alternatif pada Pemeriksaan Escherichia coli - Kalisti Meriani Papalanggi; Fath Dwisari; Puspa Amalia (Indonesian Journal of Herbal and Biomedical Research, 2025)
Escherichia coli is one of the Gram negative bacteria and the main bacteria that causes diarrhea. The identification of E. coli can be used by Gram staining using safranin. However, safranin has several limitations, which are expensive and carcinogenic. Therefore, an alternative dyes based on natural compounds such as red spinach leaves are needed. The purpose of this study was to determine the potential of soaking time variations of red spinach leaves (Amaranthus tricolor L) as an alternative dye and the effect of soaking time variations on the examination of Escherichia coli staining. This research was conducted by quasi-experiments, using purposive sampling with a total of 27 samples and safranin as positif control. The Fisher's exact statistical test obtained p-value<0.05 which stated there were difference between red spinach leaves and safranin in staining of E. coli bacteria. The present study exhibited the potency of (Amaranthus tricolor L.) as an alternative dye for E. coli staining, but had not shown better results compared to safranin.